(untitled) (Prilozi za orijentalnu filologiju, 2017)
The paper brings some observations about the translation of the Bosnian future tense into the Turkish language in Ivo Andrić’s novel The Biidge over the Drina River (both the original and the translation). The author States what in Turkish determines the choice between the two parts of binary opposition of the time sphere of futurity when the Bosnian future tense is translated, bearing in mind that, in contrast to the Bosnian language,every verb tense in the Turkish language implies modal meaning apart from temporal (i.e. the attitude of the speaker to the action he is reporting), as well as the fact that for each time sphere there are two funte verb forms opposing one another just by their modal meaning. Naturally, when translating a statement from Bosnian into Turkish, a verb tense (the corresponding member of the binary opposition) will be determined by the act of speaking itself, by the role of the statement in relation to the behaviour of the speaker (and collocutor) duiing the process of communication.